Multicultural Islamic Education Through Learning Experiences of Diverse Students in Pesantren - Moch. Iqbal; Wachid Ridwan (Jurnal Pendidikan Islam, 2026)
Pesantren, the oldest Islamic educational institution in Indonesia, has increasingly become a learning space for students from varied ethnic, cultural, and social backgrounds, creating new opportunities for multicultural Islamic education. This study explores how Islamic multicultural values are understood and implemented at Pesantren Ihyaul Qur’an in Central Bengkulu. Employing a qualitative field research design, data were gathered through observations, interviews, and documentation. The findings indicate that Pesantren Ihyaul Qur’an has transformed into a modern Islamic boarding school with a diverse student community drawn from different regions, while upholding equal treatment for all students as long as institutional rules are observed. Multicultural Islamic values are embedded in both formal academic activities and traditional pesantren learning, supported by a combination of theoretical instruction and practical application. These values are strengthened through extracurricular activities, the use of Arabic and English, and programs such as Muhadhoroh (public speaking) and Muhimmah Ta’awuniah (collaborative tasks), which promote collaboration and mutual understanding. The study concludes that the pesantren’s innovative practices, including its art-stage initiatives, effectively nurture tolerance, cooperation, and intergroup harmony. This approach provides a meaningful model for enhancing multicultural Islamic education in pesantren and other Islamic educational institutions.